Misophonia and Potential Underlying Mechanisms: A Perspective - Palumbo, Devon B.; Alsalman, Ola; De Ridder, Dirk; Song, Jae-Jin; Vanneste, Sven (Frontiers in Psychology, 2018)
There is a growing research interest in the diagnosis rate of misophonia, a condition characterized by a negative emotional/autonomic reaction to specific everyday sounds. Diagnosis of misophonia requires a thorough case history and audiological test procedures. The involvement of emotions and autonomic reactions as well as a recent functional neuroimaging study showing changes in the insula with regard to sound-evoked activity and functional connectivity suggest an abnormal connection linking the auditory, limbic, and autonomic nervous systems. Associative and non-associative learning models for understanding the underlying mechanisms of misophonia have been presented. Currently, there is no cure or pharmaceutical agent for misophonia; however, therapy programs addressing misophonia and its characteristics do exist. Investigation of comorbid conditions and other psychological therapy strategies might help to reveal more about the underlying mechanisms and potentially lead to a successful treatment method.